POLA KOMUNIKASI PEMERINTAH KOTA MAKASSAR DALAM PROGRAM PENANGANAN PANDEMI COVID-19 MELALUI MEDIA WEBSITE “covid19.go.id” UNTUK MASYARAKAT TAAT PROTOKOL KESEHATAN - Awal Juliansyah , Andi; Zelfia, Zelfia; Muttaqin, Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The aims of this study are (1) to find out the communication patterns of the Makassar government in the Covid-19 pandemic management program. (2) To learn about the media use of the Makassar government’s “covid19.go.id” website in the Covid-19 pandemic management program. The method used in this research is qualitative method. There were four informants in this study. This research lasted for one month and was located at the office of Communications and Informatics. The research method used in this study is a qualitative method. Data collection techniques through observation, interviews and documentation. Based on the research results, it can be concluded that the government of Makassar played a significant role in the handling and service of Covid-19 information through digital an non digital communication patterns in which notifications are digitally provided via websites, whatsapp social media, instagram, facebook and social media. Non digital, it is to encourage the community to use masks, wash their hands and sosial distancing